The Role of New Family Business Value Creation for Stregthening Family Business Sustainability - Purwandari, Suci; Purnomo, Singgih; Sentosa, Ilham (Jurnal Analisis Bisnis Ekonomi, 2025)
Family business research is compelling due to its significant contribution to the economy, particularly in developing countries like Indonesia. While innovation plays a crucial role in the sustainability of family businesses, its effectiveness is still influenced by succession, family involvement, and successor knowledge. Previous studies have indicated that family businesses are more innovative than non-family businesses; however, the relationship between family involvement and innovation remains inconsistent. Notably, 95% of private businesses in Indonesia are family-owned, contributing 25% to the GDP. Yet, only 30% survive into the second generation, and a mere 12% reach the third generation due to poor succession planning and weak innovation management. This research addresses the gap by developing the concept of New Family Business Value Creation (NFBVC) based on the Resource-Based View (RBV) and Sustainable Family Business Theory (SFBT) to optimize family resources for sustainable innovation. Utilizing an exploratory-predictive approach, the study involves 268 successors of small and medium-sized Batik family businesses and is analyzed using PLS-SEM. The findings are expected to provide theoretical and practical contributions to the sustainability of family businesses. This research highlights the critical role of successor knowledge, willingness, and parent-child cohesion in sustaining family businesses. By introducing New Family Business Value Creation (NFBVC), the study reinforces RBV and SFBT theories, demonstrating that Family Social Capital and value creation significantly enhance long-term business sustainability across generations. NFBVC serves as a key mediator in family business sustainability, enriching RBV and SFBT theories, and emphasizes moral-based value creation as essential for long-term business continuity across generations.